Three Notes on the Sefire Inscription (I. The šrn of Sef. I A 33; II. Sef. I A 38; III. Sef. I В 30) - Greenfield, Jonas C.
= akk. šurānu “Wildkatze”; ’n.t lies ’nr!t/’Inurta; vgl. den 105 zitierten PN mng’nrt = Mannu-kī-’Inurta; zur Konstruktion “noun x upon noun x verb”.